Analysis of the Studies Examining the Effect of Argumentation-Based Learning Implementation in Science Education - Tüysüz, Cengiz; Somuncu, Halil (Tauladan Fathimah Azzahra, 2024)
The aim of this study is to analyze the studies investigating the effect of argumentation-based learning methods on students’ academic achievement in science education in Turkey and present them in a unity. For this purpose, the document analysis method, which is one of the qualitative research methods, was used. The study included 68 master’s theses, 22 doctoral dissertations and 36 articles from the studies conducted on the subject in Turkey between 2007 and 2022. As a result of the analysis, it was determined that the most studies were conducted in 2019, the studies were mostly in the field of science, quasi-experimental designs were mostly used in these studies, achievement tests and attitude scales were mostly used to collect data, and the studies were mostly conducted at the secondary school level.